Supervisory evaluation of Pillar I and economic capital models - Dietz, Thomas (Henry Stewart Talks, 2009)
Pillar I models, The model approvement process under Pillar I, Preparing for the model assessment, Lessons learned during the assessment process, Ongoing supervision of the models, Benefits for risk based supervision, Supervisory approach to Pillar II models, Internal Models under Basel II and Solvency II